Optimization of BCG Therapy Targeting Neutrophil Extracellular Traps, Autophagy, and miRNAs in Bladder Cancer: Implications for Personalized Medicine - Mao, Chenyu; Xu, Xin; Ding, Yongfeng; Xu, Nong (Frontiers in Medicine, 2021)
Bladder cancer (BC) is the ninth most common cancer and the thirteenth most common cause of mortality worldwide. Bacillus Calmette Guerin (BCG) instillation is a common treatment option for BC. BCG therapy is associated with the less adversary effects, compared to chemotherapy, radiotherapy, and other conventional treatments. BCG could inhibit the progression and recurrence of BC by triggering apoptosis pathways, arrest cell cycle, autophagy, and neutrophil extracellular traps (NETs) formation. However, BCG therapy is not efficient for metastatic cancer. NETs and autophagy were induced by BCG and help to suppress the growth of tumor cells especially in the primary stages of BC. Activated neutrophils can stimulate autophagy pathway and release NETs in the presence of microbial pathogenesis, inflammatory agents, and tumor cells. Autophagy can also regulate NETs formation and induce production of reactive oxygen species (ROS) and NETs. Moreover, miRNAs are important regulator of gene expression. These small non-coding RNAs are also considered as an essential factor to control the levels of tumor development. However, the interaction between BCG and miRNAs has not been well-understood yet. Therefore, the present study discusses the roles of miRNAs in regulations of autophagy and NETs formation in BCG therapy in the treatment of BC. The roles of autophagy and NETs formation in BC treatment and efficiency of BCG are also discussed.